2012
DOI: 10.1155/2012/267329
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Kidney Disease and Its Association with Risk Factors in Disadvantageous Population

Abstract: The prevalence of kidney disease, particularly diabetic and hypertensive kidney disease is increasing rapidly specially in the disadvantageous group of population throughout the world. A cross sectional survey was carried out at certain selected slum areas of Mirpur in Dhaka city of Bangladesh over the period from July 2003 to June 2005, and a total of participants ranging from 15 to 65 years were studied. The analysis discovered that 4.1% of the participants were diabetic, 11.6% were hypertensive, and 7.7% ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
48
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 28 publications
(31 reference statements)
7
48
3
2
Order By: Relevance
“…The latter study was done in an area with predominant Muslim peri-urban population where the risk of CKD was more; therefore in our present study, we find relatively less prevalence of proteinuria. A cross-sectional survey was carried out at certain selected slum areas of Mirpur at Dhaka city in Bangladesh which showed proteinuria prevalence of 7.7% by the dip stick method [7] which is low compared to our study. It could be due to the fact that the other study was conducted among a younger population as the mean age of their study population was 34.4 years while the mean age of our study population was 38.5 years.…”
Section: Discussioncontrasting
confidence: 75%
“…The latter study was done in an area with predominant Muslim peri-urban population where the risk of CKD was more; therefore in our present study, we find relatively less prevalence of proteinuria. A cross-sectional survey was carried out at certain selected slum areas of Mirpur at Dhaka city in Bangladesh which showed proteinuria prevalence of 7.7% by the dip stick method [7] which is low compared to our study. It could be due to the fact that the other study was conducted among a younger population as the mean age of their study population was 34.4 years while the mean age of our study population was 38.5 years.…”
Section: Discussioncontrasting
confidence: 75%
“…Other study conducted in North Africa HTN was accounts for about 35% of causes [11]. Farag [6][7][8][9][10][11][12][13]. In Japan, Iseki et al found that 40% of ESRD caused by DM [14].…”
Section: Discussionmentioning
confidence: 99%
“…A maioria nha fi lhos, e a renda era inferior a três salários mínimos. Corrobora, portanto, com dados da literatura internacional, que parecem indicar que indivíduos mais propensos à doença renal crônica são aqueles que apresentam condições mais desfavoráveis de vida, tais como: baixa renda pessoal e familiar, baixo grau de escolaridade, condições essas que mal sa sfazem as necessidades de sobrevivência quando se leva em conta o tamanho da família e os gastos que porventura são necessários dispensar com a doença con nuamente (White et al, 2008;Fischer et al, 2010;Barros, Francisco, Zanche a, & César, 2011;Huda, Alam, & Rashid, 2012), o que pode infl uenciar também o próprio cuidado com a saúde. Questões sobre a doença, tratamento, medicamentos e dietas indicaram que muitas dessas informações são oferecidas.…”
Section: Discussionunclassified